2014
DOI: 10.1080/15504263.2014.961852
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Depressive Symptoms, and Daily Cigarette Use

Abstract: Objective It is widely known that cigarette use and depressive symptoms co-occur during adolescence and young adulthood and that there are gender differences in smoking initiation, progression, and co-occurrence with other drug use. Given that females have an earlier onset of depressive symptoms while males have an earlier onset of cigarette use, this study explored the possible bidirectional development of cigarette use and depressive symptoms by gender across the transition from adolescence to young adulthoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0
2

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 50 publications
2
7
0
2
Order By: Relevance
“…Smoking was associated with an increased risk of developing depression in women, but not in men. A relationship between cigarette use and depressive symptoms has been consistently reported [32], while gender differences in this relationship remain inconclusive [33, 34]. Smoking rates in women are lower in Japan than in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking was associated with an increased risk of developing depression in women, but not in men. A relationship between cigarette use and depressive symptoms has been consistently reported [32], while gender differences in this relationship remain inconclusive [33, 34]. Smoking rates in women are lower in Japan than in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…Women also report greater perceived risks from quitting smoking, including greater negative affect-a key feature of MDD (McKee, O'Malley, Salovey, Krishnan-Sarin, & Mazure, 2005). Moreover, though concurrent depression and cigarette consumption are comorbid across sex (John, Meyer, Rumpf, & Hapke, 2004), longitudinal data suggests that only among women are there bidirectional associations between smoking behavior and depression over time (Bares, 2014).…”
Section: Sex Differences In Biopsychosocial Predictors Of Smokingmentioning
confidence: 99%
“…In addition, adolescent smokers experience more stress than non-smoking adolescents [11]. A number of studies have shown a significant association between depression and smoking [12,13], emphasizing the importance of smoking cessation [14]. Furthermore, in non-smoking adolescents, exposure to secondhand smoke is associated with mental disorders, such as depression and anxiety [15][16][17], and this association was different according to gender [18].…”
Section: Introductionmentioning
confidence: 99%